2005
DOI: 10.1007/s00167-004-0572-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patellar height and measurement methods after valgus high tibial osteotomy

Abstract: Several controversies exist regarding the surgical difficulties and the results of total knee arthroplasty performed after failed valgus high tibial osteotomy (HTO), and the main subject is the change in patellar height that results as patella baja or infera. The purpose of this retrospective study was to evaluate patellar height after valgus HTO and the measurement methods that were actually used. Eighty-five knees that were subjected to valgus HTO were evaluated both preoperatively and postoperatively accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 27 publications
8
56
1
2
Order By: Relevance
“…To some extent, our study showed a similar distribution of patellae norma, alta and infera as reported in the literature at the site of different surgical indications [12,[30][31][32]. In some cases, our results demonstrated great variations in the determined values.…”
Section: Discussionsupporting
confidence: 87%
“…To some extent, our study showed a similar distribution of patellae norma, alta and infera as reported in the literature at the site of different surgical indications [12,[30][31][32]. In some cases, our results demonstrated great variations in the determined values.…”
Section: Discussionsupporting
confidence: 87%
“…The decrease in patellar height observed was similar to the decrease in patellar height reported after closing-wedge proximal tibial osteotomy procedures. 13,26,38,41,43,47 We also found that this significant decrease in patellar height after opening-wedge proximal tibial osteotomies happens within the first 3 postoperative months. However, only when measuring the patellar height using the Insall-Salvati index was there a significant difference in patellar height ratio between the anteromedial and posteromedial plate positions.…”
Section: Discussionmentioning
confidence: 67%
“…§ Both decreased 24,26 and increased 6 tibial slope after proximal tibial osteotomies have been reported to have a significant association with reduced patellar height.…”
mentioning
confidence: 99%
“…However, these indexes are by some authors not recommended for use in HTO patients since the osteotomy changes proximal tibial anatomy including tibial slope [25,27,30]. Instead, the use of an index with a reference point within the femur is recommended, e.g.…”
Section: Discussionmentioning
confidence: 99%